THE INFLUENCE OF FACTORS FORMING ENTREPRENEURIAL ORIENTATION ON BUSINESS PERFORMANCE OF UMKM IN THE HOBBY AND SPORTS SECTOR IN JAKARTA - Aldi Hizkia Tumiwa (Universitas Sam Ratulangi, 2023)
This study aims to determine the effect of innovativeness, proactiveness, risk-taking, competition aggressiveness, and market orientation on the business performance of MSMEs in the culinary sector in Jakarta. The culinary industry is one of the industries that has been fatally affected by COVID-19. From the news found, it was explained that the food and beverage industry in Indonesia had increased from 2020 to 2021 by 2.54 percent to IDR 775.1 trillion, the Central Statistics Agency (BPS) reported the gross domestic product (GDP) of the national food and beverage industry on basic current price (ADHB) of IDR 1.12 quadrillion in 2021. Basically, the culinary industry is a necessity for everyone, so it's not natural for it to experience a decline in performance. This research is limited to only examining the entrepreneurial orientation variables studied with innovativeness, proactiveness, risk-taking, competitive aggressiveness and market orientation variables. This research is also limited to examining the hobby and sports sector in Jakarta. The benefit of this research is to assist the government or universities in developing research on business performance. This study used 240 informants who are owners or managers of culinary SMEs in North Jakarta. The data used in this study is primary data in the form of questionnaires distributed via Google Forms.